Application of AHP Method to Cosmetic Brand Selection with Halal Labeling, Packaging and Price Criteria - Putri Alfira Ardiansyah; Nurfiah Anwar; Muslihati (Al-Fadilah: Islamic Economics Journal, 2025)
The trend and evolution of cosmetics among Indonesian women continues and never recedes from time to time, especially in the current era. With the many choices of cosmetic products, consumers often feel confused in determining which products to use. Consumers consider many things before buying something, such as price, halal labeling, packaging. This study aims to determine the application of the AHP method to the selection of cosmetic brands with the criteria of halal labeling, packaging, and price. By using the Quantitative method, data collection was carried out through an online Questionnaire (Google Form) which was distributed to all female students of UIN Alauddin Makassar with a sample of 100 respondents who met the research requirements. This study uses the AHP method and is tested or analyzed using Microsoft Excel. The results of the study show that Price is the most dominant factor influencing consumer decisions in choosing cosmetic brands, followed by Halal Labeling and Packaging. Based on the results of the study, manufacturers should pay more attention to the Price aspect to increase competitiveness in the market. Then halal labeling and packaging can be attempted to improve product quality so that it will strengthen consumer purchasing decisions in buying a product.